PENGEMBANGAN DESA WISATA BERBASIS BUDAYA DI KAWASAN BALI AGA, KECAMATAN BANJAR - I Putu Mardika (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
This article aims to examine the development of cultural-based tourism villages in the Bali Aga Region, Banjar District. The Bali Aga villages include Sidatapa, Cempaga, Tigawasa, Pedawa and Banyuseri villages which have very distinctive traditions, customs and cultures, so they deserve to be developed to attract tourists without having to change the characteristics of the village. This research is a qualitative research, with an ethnographic approach. As a result, Sidatapa Village has cultural potentials such as traditional houses, fruit rituals at Pura Desa, Briyang Agung rituals and folklore. Meanwhile, Cempaga Village has cultural characteristics such as the Kuningan Sabha, the Sakaroras Traditional House, and the Ngaben tradition. Especially for Tigawasa Village, it has cultural capital in the form of traditional houses, bamboo crafts, the tradition of wasting kidang, and tabuh rah. Pedawa Village has the traditional house of Bandung Rangki, the Ngaga Tradition, the Nguja Seed ritual, Saba Malunin, to the palm sugar craft. Banyuseri village has relics in the form of ancient inscriptions and the Mekelin Tradition. The strategy for developing cultural tourism is carried out through socialization, cooperating with academics and training for tourism awareness groups.Keywords: culture-based tourism, bali aga village region, banjar district